2012
DOI: 10.1002/bjs.8713
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of total pancreatectomy and islet autotransplantation for chronic pancreatitis

Abstract: Background: Total pancreatectomy and islet autotransplantation (TP/IAT) is a treatment option in a subset of patients with chronic pancreatitis. A systematic review of the literature was performed to evaluate the outcome of this procedure, with an attempt to ascertain when it is indicated. The impact on quality of life was poorly reported. The studies reviewed did not provide evidence for optimal timing of TP/IAT in relation to the evolution of chronic pancreatitis. Conclusion:This systematic review showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 27 publications
1
65
1
Order By: Relevance
“…As a latest systematic review conducted by K. Bramis which included five studies showed that, TP/IAT had favourable outcomes of pain reduction and can enabled a large proportion of patients to remain insulin independent [25], we recommend more centers to do this procedure to promote the development of the technology.…”
Section: Discussionmentioning
confidence: 99%
“…As a latest systematic review conducted by K. Bramis which included five studies showed that, TP/IAT had favourable outcomes of pain reduction and can enabled a large proportion of patients to remain insulin independent [25], we recommend more centers to do this procedure to promote the development of the technology.…”
Section: Discussionmentioning
confidence: 99%
“…TP has been considered as a potential option in the management of chronic pancreatitis refractory to treatment, locally advanced pancreatic cancer, multifocal or recurrent exocrine and endocrine tumours [1][2][3][4][5][6]. In addition to this, surgeons have carried out TP to treat or avoid perioperative complications, arising from pancreatic anastomotic insufficiency with or without bleeding, following pancreaticoduodenectomy or distal pancreatectomy [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…These complications may occur increasingly, while dealing with a soft pancreas during primary surgery, which may prompt some surgeons to opt for TP [4,7]. However the concern has been, about the management of these patients in a pancreatic state, with its attendant total endocrine and exocrine insufficiency [1][2][3][4][5]. This includes the complete insulin deficiency and the necessity of insulin therapy, exocrine insufficiency with steatorrhea and the need for durable pancreatic enzyme replacement and the development of steatohepatis with progressive liver failure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations